Volatility, valuation ratios, and bubbles: An empirical measure of market sentiment - Can Gao; Ian Martin (Leibniz Institute for Financial Research SAFE, 2021)
We define a sentiment indicator based on option prices, valuation ratios and interest rates. The indicator can be interpreted as a lower bound on the expected growth in fundamentals that a rational investor would have to perceive in order to be happy to hold the market. The lower bound was unusually high in the late 1990s, reflecting dividend growth expectations that in our view were unreasonably optimistic. We show that our measure is a leading indicator of detrended volume and of analysts' long-term earnings growth expectations. Our approach depends on two key ingredients. First, we derive a new valuation-ratio decomposition that is related to the Campbell and Shiller (1988) loglinearization, but which resembles the Gordon growth model more closely and has certain other advantages. Second, we introduce a volatility index that provides a lower bound on the market's expected log return.
Keywords: G10; G12; G14; 330; bubbles; Option prices; sentiment; valuation ratios; volatility